Prospects And Problems Of Electronic Marketing Application: The Nigerian Perspective - Keneth, Obi (Archives of Business Research, 2019)
This paper focused on benefits and challenges of electronic marketing application, taking insights from Nigeria. It also looked at necessary conditions that must be put in place before electronic marketing will thrive. Conclusion and recommendations were made as to how the perceived challenges facing electronic marketing adoption can be overcome.